Seasonal and long-term variability of meiofauna in the environment frequently affected by hypoxia in central part of the Gulf of Trieste - Vrišer, Borut (Annales. Series historia naturalis, 1999)
The article deals with benthic meiofauna studied for three years in central part of the Gulf of Trieste. The obtained results present meiofauna's seasonal reproduction cycles and long-term trends in these cycles...
Keywords: bentoška meiofavna; ecology; ekologija; Gulf of Trieste; meiofavna; morje; sea; sezonska dinamika; Tržaški zaliv